Mediation centrality in complex route networks of large cities of Ukraine - Кузькін, Олексій Феліксович; Лазуткін, Микола Іванович (Eastern-European Journal of Enterprise Technologies, 2012)
The mediation centrality of vertex and edges of public transit networks of large cities of Ukraine from the position of complex networks theory are calculated and character of their distribution is set